Candidate gene discovery of Botrytis cinerea resistance in grapevine based on QTL mapping and RNA-seq - Su, Kai; Zhao, Wei; Lin, Hong; Jiang, Changyue; Zhao, Yuhui; Guo, Yinshan (Frontiers in Plant Science, 2023)
Grape gray mold disease (Botrytis cinerea) is widespread during grape production especially in Vitis vinifera and causes enormous losses to the grape industry. In nature, the grapevine cultivar ‘Beta ‘ (Vitis riparia × Vitis labrusca) showed high resistance to grape gray mold. Until now, the candidate genes and their mechanism of gray mold resistance were poorly understood. In this study, we firstly conducted quantitative trait locus (QTL) mapping for grape gray mold resistance based on two hybrid offspring populations that showed wide separation in gray mold resistance. Notably, two stable QTL related to gray mold resistance were detected and located on linkage groups LG2 and LG7. The phenotypic variance ranged from 6.86% to 13.70% on LG2 and 4.40% to 11.40% on LG7. Combined with RNA sequencing (RNA-seq), one structural gene VlEDR2 (Vitvi02g00982) and three transcription factors VlERF039 (Vitvi00g00859), VlNAC047 (Vitvi08g01843), and VlWRKY51 (Vitvi07g01847) that may be involved in VlEDR2 expression and grape gray mold resistance were selected. This discovery of candidate gray mold resistance genes will provide an important theoretical reference for grape gray mold resistance mechanisms, research, and gray mold-resistant grape cultivar breeding in the future.